Macrophages in vascular inflammation – From atherosclerosis to vasculitis. (May 2015) - Shirai, Tsuyoshi; Hilhorst, Marc; Harrison, David G.; Goronzy, Jörg J.; Weyand, Cornelia M.
Abstract The spectrum of vascular inflammatory disease ranges from atherosclerosis and hypertension, widespread conditions affecting large proportions of the population, to the vasculitides, rare syndromes leading to fast and irreversible organ failure. Atherosclerosis progresses over decades, inevitably proceeding through multiple phases of disease and causes its major complications when the vessel wall lesion ruptures, giving rise to lumen-occlusive atherothrombosis. Vasculitides of medium and large arteries progress rapidly, causing tissue ischemia through lumen-occlusive intimal hyperplasia. In both disease entities, macrophages play a decisive role in pathogenesis, but function in the context of other immune cells that direct their differentiation and their functional commitments. In atherosclerosis, macrophages are involved in the removal of lipids and tissue debris and make a critical contribution to tissue damage and wall remodeling. In several of the vasculitides, macrophages contribute to granuloma formation, a microstructural platform optimizing macrophage–T-cell interactions, antigen containment and inflammatory amplification. By virtue of their versatility and plasticity, macrophages are able to promote a series of pathogenic functions, ranging from the release of cytokines and enzymes, the production of reactive oxygen species, presentation of antigen and secretion of tissue remodeling factors. However, as short-lived cells that lack memory, macrophages are also amendable to reprogramming, making them promising targets for anti-inflammatory interventions.